Focus Issue on Squamous Cell Carcinoma: Practical Concerns Regarding the 7th Edition AJCC Staging Guidelines. (10th October 2010) - Buethe, D.; Warner, C.; Miedler, J.; Cockerell, C. J.
Abstract : The 7th edition of the AJCC Cancer Staging Manual represents a dramatic shift in the way that cutaneous squamous cell carcinoma (cSCC) is staged, in that it is first attempt to incorporate evidence-based medicine into the staging guidelines for cSCC. In our opinion, the changes made to the seventh edition represent a significant improvement over previous editions and will ultimately lead to improved patient stratification, more accurate prognostic data, and a better framework to guide clinical decision making. However, there are a number of issues within the latest guidelines that require clarification or are impractical for clinical practice. The purpose of this paper is to highlight the key changes to the 6th edition staging manual as they pertain to cSCC, to point out impractical component of the 7th edition and/or aspects that require further clarification, and to make recommendations that address any current shortcomings to improve subsequent editions. Specific focus will be given to the inclusion of separate guidelines for cSCC and Merkel cell carcinoma (MCC), the incorporation of high-risk factors as modifiers of T stage, the addition of new guidelines for advanced T stage, and the changes in stratification of lymph node status. This paper is modified from a more comprehensive treatment of the staging of nonmelanoma skin cancer by Warner and Cockerell entitled "The new 7th edition American joint committee on cancer staging of cutaneous nonmelanoma skin cancer: a critical review, " in the American Journal of Clinical Dermatology (paper accepted, pending publication).